Perceptions, stigma, and coping mechanisms among mothers with postpartum depression in Malaysia - Muhammad Danial bin Dasris; Asbah Razali; Rosya Izyanie Shamshudeen; Nurhamizah Hashim; Akhmad Mansur (Faculty of Social and Political Science, Universitas Airlangga, 2026)
In Malaysia, postpartum depression (PPD) is often associated with social stigma. This study examines mothers’ perceptions of postpartum depression and identifies the barriers they face in dealing with stigma and one of the responsibilities of society using qualitative methods. Using thematic analysis to do the research, this study focuses on six mothers from urban communities in Klang Valley, Malaysia, who were selected according to a snowball sampling procedure. There are three new findings of the research that were reported, the awareness of postpartum depression remains limited to affected mothers who are often stigmatized because they are emotionally weak. The second is postnatal depression, which affects mothers’ emotional stability, marriage, work performance, and housekeeping jobs due to a lack of support from the family, and social stereotypes also play an important role. The third study indicates that mothers develop coping mechanisms, such as emotional support from partners and family members and two-way communication, to reduce stigma and maintain their mental health. The conclusion of this study shows that awareness regarding postpartum depression is still low, and that there were negative views, which may limit the social support and treatment needed. Therefore, interventions are needed to help mothers facing postpartum depression.